2016
DOI: 10.1177/1457496916631855
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Size of Invasive Breast Cancer on Magnetic Resonance Imaging and Conventional Imaging (Mammogram/Ultrasound): Comparison with Pathological Size and Clinical Implications

Abstract: Background and Aim: in landspitali university hospital, magnetic resonance imaging is used non-selectively in addition to mammogram and ultrasound in the preoperative assessment of breast cancer patients. The aim of this study was to assess invasive tumor size on imaging, compare with pathological size and evaluate the impact of magnetic resonance imaging on the type of surgery performed.Material and Methods: all women with invasive breast cancer, diagnosed in iceland, between 2007 and 2009 were reviewed retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
0
16
2
Order By: Relevance
“…While in our study, the size was underestimated in 20.5% and overestimated in 23.9% of cases, Haraldsdottir et al [8] and Grimsby et al [10] underestimated size in 4.6 and 15% of cases and overestimated in 7.5 and 33% of cases, respectively. The presence of a single DCIS [7, 28] or associated with an invasive component was cited as a possible cause of overestimation of tumour size [10]; in our study, this was only found for high-grade DCIS, which is known to enhance on MRI, even in the lack of neoangiogenesis [29].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…While in our study, the size was underestimated in 20.5% and overestimated in 23.9% of cases, Haraldsdottir et al [8] and Grimsby et al [10] underestimated size in 4.6 and 15% of cases and overestimated in 7.5 and 33% of cases, respectively. The presence of a single DCIS [7, 28] or associated with an invasive component was cited as a possible cause of overestimation of tumour size [10]; in our study, this was only found for high-grade DCIS, which is known to enhance on MRI, even in the lack of neoangiogenesis [29].…”
Section: Discussioncontrasting
confidence: 79%
“…Because of this difference, we chose a 20% concordance value between MRI and histology, rather than an absolute figure. Unlike other teams, we found it more informative to establish a percentage match threshold of histological tumour size and not a fixed difference regardless of cancer size (roughly 5 mm [7, 10] or 10 mm [8] of the size determined by histology). Indeed, this calculation allows us to have very similar real measurements for small tumours (e.g.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Receptor status 25,26 in conjunction with extent of disease 24 is important when considering neoadjuvant therapy for ILCs, especially when breast conservation is considered 24,2729 . Breast ultrasound is a widely available modality and can be used as a complement to further characterize lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, most studies conclude that size estimations with MRI are more reliable than those with clinical examination, mammography, or US. Accuracy decreases in larger cancers and is worse in NME than in mass lesions (75)(76)(77). It is important to realize that the pathologic reference standard has substantial limitations.…”
Section: Breast Lesion Evaluation At Breast Mrimentioning
confidence: 99%